(untitled) (New York, 2005)
A major revision of this problem-oriented text, covering common problems, trauma, and non-trauma emergencies in a popular, quick-access format. Features clinically focused discussion of diagnosing and managing common emergency problems, extensive algorithms to guide quick management, a comprehensive table of drugs commonly used in the ER, and illustrations, including ultrasound and CT images.
Keywords: Thuốc,Emergency medicine